2014
DOI: 10.1186/1472-6823-14-72
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of a preparation of vitamins, minerals and trace elements in diabetic rats: a gender difference

Abstract: BackgroundAlthough multivitamin products are widely used as dietary supplements to maintain health or as special medical food in certain diseases, the effects of these products were not investigated in diabetes mellitus, a major cardiovascular risk factor. Therefore, here we investigated if a preparation of different minerals, vitamins, and trace elements (MVT) for human use affects the severity of experimental diabetes.MethodsTwo days old neonatal Wistar rats from both genders were injected with 100 mg/kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…CLE contains diverse types of chemical constituents, such as polyphenols [ 9 ], minerals, dietary fiber, vitamin A, vitamin C, and several essential unsaturated fatty acids [ 10 ]. Their anti-diabetic activities have already been reported [ 28 , 29 ]. The synergistic actions of such components could effectively regulate blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…CLE contains diverse types of chemical constituents, such as polyphenols [ 9 ], minerals, dietary fiber, vitamin A, vitamin C, and several essential unsaturated fatty acids [ 10 ]. Their anti-diabetic activities have already been reported [ 28 , 29 ]. The synergistic actions of such components could effectively regulate blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from the saphenous vein after overnight fasting. Blood glucose level was immediately determined by a standard glucose meter in duplicates (Accutrend GCT, Roche Diagnostics, Mannheim, Germany) as described previously [ 33 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…To monitor the effect of cholesterol and cholic acid enriched diet on the endocrine pancreas, plasma insulin levels were measured by an enzyme immunoassay (Mercodia, Ultrasensitive Rat Insulin ELISA) in duplicates according to the manufacturer’s instructions as described previously [ 33 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The injection of neonatal rats with streptozotocin (STZ) is a well characterized and recognized model of diabetes mellitus [ 24 27 ]. This model has been particularly characterized in detail in our previous study [ 14 ]. STZ is toxic especially to pancreatic β-cells.…”
Section: Methodsmentioning
confidence: 99%
“…However, the literature is limited and controversial on the potential beneficial effects of these complex preparations containing more than 3 components on disease progression [ 12 16 ]. We have recently shown that chronic treatment with a MVT preparation improved well-established diagnostic markers of DM such as fasting blood glucose, HbA1c, glucose tolerance, and serum insulin levels in male diabetic rats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%